Consumers as Naive Physicists: How Visual Entropy Cues Shift Temporal Focus and Influence Product Evaluations - Biliciler, Gunes; Raghunathan, Rajagopal; Ward, Adrian F (Journal of Consumer Research, 2022)
Abstract Marketers often use images to promote their products. For example, an advertisement for kitchen tools might display the tools alongside various ingredients, or an advertisement for a bookstore might showcase pictures of the store’s interior. One underlying visual characteristic of such images is the degree of “entropy”—or disorder—in their content. Motivated by a fundamental principle from physics—namely, that entropy can only increase over time—the present research examines how entropy influences consumers’ judgments and decisions. Across two pilot studies and five experiments, we find that while high-entropy images shift consumers’ temporal focus to the past, low-entropy images shift their temporal focus to the future. These entropy-induced shifts in temporal focus influence consumers’ decisions. Specifically, consistent with the notion of “fit fluency,” we find that consumers evaluate past-related (e.g., vintage) products more favorably when they are accompanied by high-entropy images and future-related (e.g., futuristic) products more favorably when they are accompanied by low-entropy images. We discuss the theoretical and managerial implications of our findings.